Holistic Approach in Correctional Education (HACE) Training Module for Prison’s Vocational Instructors: Report of Peninsular Region - Rohana, Hamzah; Muhamad Afzamiman, Aripin; Sarimah, Ismail (2016)
The current correctional system under Malaysian Prison Department (Pride) has implement vocational programme as an alternative to reduce recidivism cases. However, training for inmates requires a holistic approach from the instructors as it is not like ordinary vocational education training (VET) in normal institutions. Due to that, a Holistic Approach in Correctional Education (HACE) Training Module for prisons’ vocational instructors has been developed and proposed to Malaysian Prison Department as a training and exposure. The objective of this article is to report the implementation of HACE Training Module for the first and second series in Malaysian Peninsular region. Quantitative results by Pride’s Course Evaluation Form had been used with some written feedback. The results from this report showed that vocational instructors who have attended the module, has a very good perception in term of knowledge and benefit gains towards their professionalism in teaching.